Gradient-doped lithium manganese iron phosphate positive electrode material, preparation method and application thereof

CN120809776BActive Publication Date: 2026-10-09SHENZHEN DYNANONIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510898619.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2026-10-09
Estimated Expiration
2045-06-30

AI Technical Summary

Technical Problem

[0005]本申请的目的在于提供一种梯度掺杂型磷酸锰铁锂正极材料及其制备方法与应用,旨在解决现有技术中无法有效改善橄榄石型富锰磷酸盐正极材料的循环稳定性及电压衰减的问题

Benefits of technology

[0037] The gradient-doped lithium manganese iron phosphate cathode material provided in the first aspect of this application adopts a core-shell structure with mixed doping elements distributed in a gradient increasing manner, creating a special chemical environment inside the material. On the one hand, the change in concentration gradient effectively alleviates the lattice distortion problem, enhances the structural stability of the material, reduces phase transitions and volume changes during cycling, thereby significantly improving the cycling performance of the material. On the other hand, the gradient distribution of doping elements optimizes the charge transport path, reduces asynchronous reactions between particles, effectively suppresses voltage decay during charging and discharging, and improves energy density. At the same time, the introduction of high entropy can suppress the reaction of Mn... 3+ The Jahn-Teller distortion caused by the disproportionation reaction improves the structural stability of the material and prevents the accumulation of dopants during cycling. On the other hand, the high-entropy environment may reduce the activation energy of Li+ migration and improve the kinetics, which is beneficial to improving the overall performance of lithium manganese iron phosphate cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120809776B_ABST
    Figure CN120809776B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion batteries, in particular to a gradient-doped lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. A gradient-doped lithium manganese iron phosphate positive electrode material is provided, the gradient-doped lithium manganese iron phosphate positive electrode material comprises mixed doping elements, the mixed doping elements at least comprise four different elements; and the gradient-doped lithium manganese iron phosphate positive electrode material is in a core-shell structure, and the mixed doping elements are distributed in a gradient increasing mode along the core-shell structure. The gradient-doped lithium manganese iron phosphate positive electrode material provided adopts a core-shell structure and the mixed doping elements are distributed in a gradient increasing mode, not only through the change of the concentration gradient, but also effectively alleviating the lattice distortion problem, enhancing the structural stability of the material, reducing the phase change and volume change in the cycle process, optimizing the charge transport path, reducing the asynchronous reaction between particles, effectively inhibiting the voltage attenuation in the charging and discharging process, and improving the energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of lithium-ion battery technology, and particularly relates to a gradient-doped lithium manganese iron phosphate cathode material, its preparation method and application. Background Technology

[0002] In the lithium-ion battery technology system, lithium iron phosphate (LFP) cathode materials stand out due to their high intrinsic safety, excellent cycle stability, and environmentally friendly characteristics, making them the core choice for new energy vehicle power systems and large-scale energy storage power stations. However, limited by its theoretical specific capacity limit, it is difficult to meet the development needs of lightweight and long-range terminal devices in high-power applications such as drones and high-end power tools, which have stringent energy density requirements. Therefore, there is an urgent need to develop new cathode material systems that combine high energy and high safety.

[0003] To overcome this technological bottleneck, researchers developed a lithium manganese iron phosphate (LMFP) material system through a partial Fe-Mn element substitution strategy. Benefiting from Mn... 2+ / Mn 3+ The higher redox potential enabled this material system to achieve a significant increase in energy density. However, with the increase of the manganese doping ratio, the material system faces multiple performance challenges: firstly, Mn... 3+ The Jahn-Teller effect causes severe lattice distortion, leading to frequent phase transitions and volume changes during cycling, thus compromising the material's structural stability. Secondly, the increased differences in interparticle reaction kinetics cause a tilt in the charge / discharge voltage plateau, resulting in voltage decay and energy density loss. Thirdly, under long-cycle conditions and high-rate charge / discharge, the capacity decay rate of the material accelerates significantly, making it difficult to meet the cycle life requirements of practical applications. Although existing research has attempted to suppress the Jahn-Teller effect by uniformly doping with elements such as Ti, Mg, and V, the suppression effect has significant limitations, and the improvement effect on voltage decay has not met expectations. Furthermore, the microscopic mechanism of voltage decay still lacks a systematic theoretical explanation.

[0004] It is evident that traditional doping strategies cannot effectively improve the cycle stability and voltage decay of olivine-type manganese-rich phosphate cathode materials, and therefore cannot meet practical application requirements. Summary of the Invention

[0005] The purpose of this application is to provide a gradient-doped lithium manganese iron phosphate cathode material, its preparation method and application, aiming to solve the problem that the existing technology cannot effectively improve the cycle stability and voltage decay of olivine-type manganese-rich phosphate cathode materials.

[0006] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0007] In a first aspect, this application provides a gradient-doped lithium manganese iron phosphate cathode material, which includes mixed doping elements, including at least four different elements; and the gradient-doped lithium manganese iron phosphate cathode material has a core-shell structure, with the mixed doping elements distributed in a gradient increasing manner along the core-shell structure.

[0008] In some embodiments, the gradient-increasing distribution means that the concentration of the mixed dopant elements gradually increases from the core to the shell; and satisfies the following condition:

[0009] (a) In the core interface region: the doping concentration is 1% to 5%;

[0010] (b) In the intermediate transition region: the doping amount is 2.5% to 10%;

[0011] (c) In the shell interface region: the doping amount is 5% to 15%.

[0012] In some embodiments, the mixed doping elements include at least four different elements:

[0013] At least one of the rare earth elements La and Y;

[0014] At least one of the transition metal elements Ti, V, Ni, and Cr;

[0015] At least one of the transition metal elements Zn, Zr, and Nb;

[0016] At least one of the light metal elements Mg and Al;

[0017] Furthermore, the atomic percentage of each element is 0.02 to 0.04.

[0018] In some embodiments, the configurational entropy ΔS of the gradient-doped lithium manganese iron phosphate cathode material is 1.0R to 1.5R.

[0019] In some embodiments, the particle size distribution of the gradient-doped lithium manganese iron phosphate cathode material satisfies: D 10 ≤0.5μm, D 50 ≤1.0μm, D 90 ≤4.0μm.

[0020] In some embodiments, the gradient-doped lithium manganese iron phosphate cathode material further includes a carbon coating layer, wherein the thickness of the carbon coating layer is 4nm-8nm.

[0021] In some embodiments, the carbon content is 1.2 wt% to 1.5 wt% based on the total mass of the gradient-doped lithium manganese iron phosphate cathode material as 100%.

[0022] In some embodiments, the mixed doping elements are selected from combinations of Al, V, Ni, Zn, and Y.

[0023] Secondly, this application provides a method for preparing a gradient-doped lithium manganese iron phosphate cathode material, comprising the following steps:

[0024] Provide precursors containing low concentrations of mixed doped elements;

[0025] The precursor is subjected to a sintering process to obtain a sintered material.

[0026] A composite carbon source, a mixed metal source containing doped elements, and a primary sintering material are mixed, granulated, and subjected to a secondary sintering process to obtain a gradient-doped lithium manganese iron phosphate cathode material.

[0027] In some embodiments, the precursor containing a low concentration of mixed dopant elements has a mixed dopant element content of 1.0% to 1.5%.

[0028] In some embodiments, the total mass of the calcined material is 100%, and the carbon content is 0.01wt% to 0.1wt%.

[0029] In some embodiments, the composite carbon source is selected from at least two of glucose, PEG, and oleic acid.

[0030] In some embodiments, the temperature of the first sintering is 500℃~600℃, the heating rate is 5℃ / min~7℃ / min, and the time is 6h~10h.

[0031] In some embodiments, the secondary sintering temperature is 750℃~800℃, the heating rate is 5℃ / min~7℃ / min, and the time is 10h~16h.

[0032] In some embodiments, the step of mixing the composite carbon source, the mixed metal source containing doped elements, and the calcined material is carried out by wet ball milling, wherein the ball-to-material ratio is 3 / 1 to 6 / 1, the ball milling time is 2h to 6h, and the ball milling solvent is pure water or a mixture of water and anhydrous ethanol.

[0033] In some embodiments, the solid content of the slurry obtained by mixing is 40% to 50%, and the particle size D of the slurry is... 50 The range is 0.3μm to 0.6μm.

[0034] In some embodiments, prior to granulation, slurries of different particle sizes are mixed in a specific ratio, wherein particle size D 50 The slurry with a particle size of 0.28μm to 0.32μm accounts for 20% to 30%, and the particle size D 50 The slurry with a particle size of 0.58μm to 0.62μm accounts for 70% to 80%.

[0035] Thirdly, this application discloses a lithium-ion battery positive electrode sheet comprising the aforementioned gradient-doped lithium manganese iron phosphate positive electrode material, a conductive agent, and a binder.

[0036] Fourthly, this application discloses a lithium-ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode adopts the above-mentioned lithium-ion battery positive electrode sheet.

[0037] The gradient-doped lithium manganese iron phosphate cathode material provided in the first aspect of this application adopts a core-shell structure with mixed doping elements distributed in a gradient increasing manner, creating a special chemical environment inside the material. On the one hand, the change in concentration gradient effectively alleviates the lattice distortion problem, enhances the structural stability of the material, reduces phase transitions and volume changes during cycling, thereby significantly improving the cycling performance of the material. On the other hand, the gradient distribution of doping elements optimizes the charge transport path, reduces asynchronous reactions between particles, effectively suppresses voltage decay during charging and discharging, and improves energy density. At the same time, the introduction of high entropy can suppress the reaction of Mn... 3+ The Jahn-Teller distortion caused by the disproportionation reaction improves the structural stability of the material and prevents the accumulation of dopants during cycling. On the other hand, the high-entropy environment may reduce the activation energy of Li+ migration and improve the kinetics, which is beneficial to improving the overall performance of lithium manganese iron phosphate cathode materials.

[0038] The method for preparing gradient-doped lithium manganese iron phosphate cathode material provided in the second aspect of this application employs a process of first preparing a precursor containing low-concentration mixed dopant elements, followed by two sintering treatments. This process allows for precise control of the distribution of dopant elements and the material's structure. The first sintering treatment can initially form the material's crystal structure and basic properties, while the second sintering, combined with a composite carbon source and a mixed metal source containing dopant elements, further optimizes the material's structure and properties, achieving gradient doping and carbon coating effects, which is beneficial for large-scale industrial production.

[0039] The lithium-ion battery positive electrode sheet provided in the third aspect of this application comprises the aforementioned high-performance gradient-doped lithium manganese iron phosphate positive electrode material, combined with a conductive agent and a binder, which can form a good electrode structure and ensure the conductivity and stability of the electrode.

[0040] The lithium-ion battery provided in the fourth aspect of this application, which uses the positive electrode sheet, has higher energy density, longer cycle life and better rate performance due to the improved performance of the positive electrode material. It has a wider application prospect in the fields of new energy vehicles and energy storage systems and can meet the market demand for high-performance lithium-ion batteries. Attached Figure Description

[0041] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0042] Figure 1 These are XRD analysis diagrams of the samples provided in Examples 1, 2 and the comparative examples of this application. Detailed Implementation

[0043] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0044] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0045] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0046] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0047] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0048] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as μg, mg, g, or kg.

[0049] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0050] The first aspect of this application provides a gradient-doped lithium manganese iron phosphate cathode material, which includes mixed doping elements, including at least four different elements; and the gradient-doped lithium manganese iron phosphate cathode material has a core-shell structure, with the mixed doping elements distributed in a gradient increasing manner along the core-shell structure.

[0051] The gradient-doped lithium manganese iron phosphate cathode material provided in the first aspect of this application adopts a core-shell structure and the mixed doping elements are distributed in a gradient increasing manner, resulting in a special chemical environment inside the material. On the one hand, the change in concentration gradient effectively alleviates the lattice distortion problem, enhances the structural stability of the material, reduces phase transitions and volume changes during cycling, thereby significantly improving the cycling performance of the material. On the other hand, the gradient distribution of doping elements optimizes the charge transport path, reduces asynchronous reactions between particles, effectively suppresses voltage decay during charging and discharging, and improves energy density. At the same time, the introduction of high entropy can suppress the reaction of Mn... 3+ The Jahn-Teller distortion caused by the disproportionation reaction improves the structural stability of the material and prevents the accumulation of dopants during cycling. On the other hand, the high-entropy environment may reduce the activation energy of Li+ migration and improve the kinetics, which is beneficial to improving the overall performance of lithium manganese iron phosphate cathode materials.

[0052] Among them, doping with at least four different elements in lithium manganese iron phosphate cathode materials can achieve electronic structure regulation, enhance interface stability, and increase entropy. Compared with traditional doping strategies, high-entropy doping emphasizes proportional synergistic regulation rather than flexible concentration adjustment. The effects that high-entropy doping may bring include (1) cocktail effect - complex synergistic interactions achieve precise regulation of material performance; (2) local regulation effect - the special chemical environment formed by multiple components optimizes charge transport; (3) structural stability - reducing lattice strain and suppressing phase transition by forming a high-entropy configuration; (4) high disorder characteristics - the increase of disorder in the internal environment of the material improves electrochemical performance; (5) entropy expansion effect - multiple elements lead to an increase in entropy in a specific region.

[0053] Furthermore, the gradient-doped lithium manganese iron phosphate cathode material has a core-shell structure, with the mixed doping elements distributed in a gradient increasing manner along the core-shell structure.

[0054] In some embodiments, the gradient-increasing distribution means that the concentration of the mixed dopant elements gradually increases from the core to the shell; and satisfies the following condition:

[0055] (a) In the core interface region: the doping amount is 1% to 5%; the core doping amount is relatively small, and the stress caused by lattice distortion is small.

[0056] (b) In the intermediate transition region: the doping amount is 2.5% to 10%; to avoid large local stress differences caused by the large difference in doping amount between the inside and outside, and to play a buffering role.

[0057] (c) In the shell interface region: the doping amount is 5% to 15%. The shell has a relatively high doping amount, and the stress caused by lattice distortion is large, but the stress of the shell can be released.

[0058] The concentration of mixed doping elements gradually increases from the core to the shell, with each region exhibiting a specific doping range. This precise concentration gradient ensures a lower doping level in the core region, maintaining the material's basic electrochemical activity; while the doping levels gradually increase in the intermediate transition and shell regions, further optimizing the material's surface properties and ion diffusion performance. For example, a higher doping level in the shell region can form a stable interface layer, enhancing the material's compatibility with the electrolyte, reducing side reactions, and accelerating lithium-ion diffusion, thereby improving the material's performance under high-rate charge-discharge conditions.

[0059] In some specific embodiments, the doping amount of the mixed dopant element in the core interface region includes, but is not limited to, typical but non-limiting values ​​such as 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, 2.7%, 3.0%, 3.2%, 3.5%, 3.7%, 4.0%, 4.2%, 4.5%, 4.7%, and 5.0%.

[0060] In some specific embodiments, the doping amount of the mixed dopant element in the intermediate transition region includes, but is not limited to, typical but non-limiting values ​​such as 2.5%, 2.7%, 3.0%, 3.2%, 3.5%, 3.7%, 4.0%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.7%, 6.0%, 6.2%, 6.5%, 6.7%, 7.0%, 7.2%, 7.5%, 7.7%, 8.0%, 8.2%, 8.5%, 8.7%, 9.0%, 9.2%, 9.5%, 9.7%, and 10%.

[0061] In some specific embodiments, the doping amount of the mixed dopant element in the shell interface region includes, but is not limited to, typical but non-limiting values ​​such as 5%, 5.2%, 5.5%, 5.7%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.7%, 8%, 8.2%, 8.5%, 8.7%, 9.0%, 9.2%, 9.5%, 9.7%, 10%, 10.2%, 10.5%, 10.7%, 11%, 11.2%, 11.5%, 11.7%, 12%, 12.2%, 12.5%, 12.7%, 13%, 13.2%, 13.5%, 13.7%, 14%, 14.2%, 14.5%, 14.7%, and 15%.

[0062] In some embodiments, the mixed doping elements include at least four different elements:

[0063] At least one of the rare earth elements La and Y;

[0064] At least one of the transition metal elements Ti, V, Ni, and Cr;

[0065] At least one of the transition metal elements Zn, Zr, and Nb;

[0066] At least one of the light metal elements Mg and Al.

[0067] Mixed doping elements include combinations of rare earth elements, various transition metal elements, and light metal elements, resulting in synergistic effects among different types of elements. Rare earth elements such as La or Y, acting as ions, can lower the Li+ migration barrier and regulate oxygen vacancy concentration through polarization effects. Transition metal elements such as Ti, V, Ni, or Cr can improve electronic conductivity, suppress Jahn-Teller distortion, and widen the lithium interlayer spacing, which is beneficial for adjusting the electronic structure of the material and optimizing ion diffusion channels. Transition metal elements such as Zn, Zr, or Nb form a stable oxide framework, which can suppress oxygen vacancy generation and enhance Li+ diffusion channels. Light metal elements such as Mg or Al can form covalent bonds with oxygen, enhancing structural rigidity and suppressing Mn. 3+ The disproportionation reaction reduces the volume expansion of the cycle. It can be seen that the synergistic effect of multiple elements not only effectively inhibits Mn but also reduces the volume expansion of the cycle. 3+ It also comprehensively improves the overall electrochemical performance of materials, such as increasing charge and discharge efficiency, extending cycle life, and increasing energy density.

[0068] Furthermore, an atomic percentage of 0.02 to 0.04 for each element helps to avoid capacity loss in the cathode material due to excessive doping. In some specific embodiments, the atomic percentage of each element includes, but is not limited to, typical but non-limiting values ​​such as 0.02, 0.03, and 0.04.

[0069] In some embodiments, the configurational entropy ΔS of the gradient-doped lithium manganese iron phosphate cathode material is 1.0R to 1.5R. Here, R is a gas constant connecting the microscopic and macroscopic scales, standardizing the entropy calculation. R = 8.314 J / mol / K.

[0070] A configurational entropy ΔS of 1.0R to 1.5R indicates that the material is in a high-entropy state. Uniform element distribution can reduce Gibbs free energy, improve phase stability, and suppress phase transitions and particle breakage during cycling. In some specific embodiments, the entropy value ΔS of gradient-doped lithium manganese iron phosphate cathode materials includes, but is not limited to, typical but non-limiting values ​​such as 1.0R, 1.1R, 1.2R, 1.3R, 1.4R, and 1.5R.

[0071] In some embodiments, the particle size distribution of the gradient-doped lithium manganese iron phosphate cathode material satisfies: D 10 ≤0.5μm, D 50 ≤1.0μm, D 90 ≤4.0μm. Based on the particle size distribution, it can be seen that the provided cathode material exhibits a narrow particle size distribution, which ensures good electrode coating uniformity and reduces localized stress concentration. Smaller particle size also helps shorten the lithium-ion diffusion path, improving rate performance.

[0072] In some embodiments, the gradient-doped lithium manganese iron phosphate cathode material further includes a carbon coating layer, wherein the thickness of the carbon coating layer is 4 nm to 8 nm. An ultrathin carbon coating layer is beneficial for balancing conductivity and lithium-ion transport resistance. In some specific embodiments, the thickness of the carbon coating layer includes, but is not limited to, typical but not limiting values ​​such as 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, and 8 nm.

[0073] In some embodiments, the carbon content is 1.2 wt% to 1.5 wt% based on 100% of the total mass of the gradient-doped lithium manganese iron phosphate cathode material. Precise control of the carbon content avoids excessive carbon reducing the volumetric energy density while providing a continuous conductive network. In some specific embodiments, the carbon content, based on 100% of the total mass of the gradient-doped lithium manganese iron phosphate cathode material, includes, but is not limited to, typical but non-limiting values ​​such as 1.2 wt%, 1.3 wt%, 1.4 wt%, and 1.5 wt%.

[0074] In some embodiments, the mixed doping elements are selected from combinations of Al, V, Ni, Zn, and Y. The provided specific combinations (Al / V / Ni / Zn / Y) create complementary effects. Al3+-Y 3 +Stable oxygen framework, Ni 2 +-V 3 + Construct dual transmission channels, Zn 2+ Overcoming the bottleneck in ion diffusion could potentially lead to a triple breakthrough in "structure-kinetics-interface".

[0075] A second aspect of this application provides a method for preparing a gradient-doped lithium manganese iron phosphate cathode material, comprising the following steps:

[0076] S01. Provide a precursor comprising a low concentration of mixed doped elements;

[0077] S02. The precursor is subjected to a sintering process to obtain a sintered material;

[0078] S03. The composite carbon source, the mixed metal source containing doped elements, and the primary sintering material are mixed, granulated, and subjected to secondary sintering to obtain a gradient-doped lithium manganese iron phosphate cathode material.

[0079] The method for preparing gradient-doped lithium manganese iron phosphate cathode material provided in the second aspect of this application employs a process of first preparing a precursor containing low-concentration mixed dopant elements, followed by two sintering treatments. This process allows for precise control of the distribution of dopant elements and the material's structure. The first sintering treatment can initially form the material's crystal structure and basic properties. The second sintering treatment, combined with a composite carbon source and a mixed metal source containing dopant elements, further optimizes the material's structure and properties, achieving gradient doping and carbon coating effects, which is beneficial for large-scale industrial production.

[0080] In step S01, a precursor containing a low concentration of mixed dopant elements is provided. The precursor can be prepared using any one of the following methods: liquid phase method, solid phase method, or precipitation method.

[0081] In some embodiments, the precursor containing a low concentration of mixed dopant elements has a mixed dopant element content of 1.0% to 5.0%. In some specific embodiments, the mixed dopant element content in the precursor containing a low concentration of mixed dopant elements includes, but is not limited to, typical but not limiting values ​​such as 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5%.

[0082] In some specific embodiments, a method for preparing a precursor with low concentrations of mixed doped elements includes the following steps: weighing appropriate amounts of lithium source, manganese source, iron source, and phosphorus source according to stoichiometric ratios, and adding a carbon source and various metal ion dopants to obtain an LMFP low-doped precursor. The preparation of the LFMP low-doped precursor can employ existing processes such as the sol-gel method and the self-heating evaporation liquid phase method.

[0083] The stoichiometric ratio of each raw material is Li:(Mn+Fe):P = (1.02~1.06):1:(1.01~1.04). The lithium source includes, but is not limited to, lithium carbonate or lithium hydroxide; the manganese source includes, but is not limited to, manganese nitrate or manganese acetate; the iron source includes, but is not limited to, ferric nitrate; and the phosphorus source includes, but is not limited to, ammonium dihydrogen phosphate or diammonium hydrogen phosphate.

[0084] The various metal ion dopants are selected from mixtures of the aforementioned elements. In some specific embodiments, the various metal ion dopants are selected from dopant elements Al, V, Ni, Zn, and Y, each using oxides or nitrates at a corresponding atomic percentage of 0.005 to 0.01.

[0085] In some embodiments, the total mass of the first-burned material is 100%, and the carbon content is 0.01wt% to 0.1wt%. Controlling the carbon content of the first-burned material to a low level ensures that an excessively thick carbon coating layer is not formed, which is beneficial for subsequent gradient coating.

[0086] In step S02, the precursor is subjected to a sintering process to obtain a sintered material.

[0087] In some embodiments, the temperature of the first sintering is 500℃~600℃, the heating rate is 5℃ / min~7℃ / min, and the time is 6h~10h.

[0088] In some specific embodiments, the sintering temperature for a single sintering includes, but is not limited to, typical but non-limiting values ​​such as 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, and 600°C.

[0089] In some specific embodiments, the sintering time for one sintering session includes, but is not limited to, typical but non-limiting values ​​such as 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, and 10h.

[0090] In step S03, the composite carbon source, the mixed metal source containing doped elements, and the primary sintering material are mixed, granulated, and subjected to secondary sintering to obtain a gradient-doped lithium manganese iron phosphate cathode material.

[0091] In some embodiments, the composite carbon source is selected from at least two of glucose, PEG, and oleic acid. In some embodiments, the amount of composite carbon source added, based on 100% of the total weight of the dicalcined product, includes, but is not limited to, 1.2 wt% to 1.5 wt%.

[0092] In some embodiments, in the mixed metal source containing doped elements, multiple metal ion dopants are selected from a mixture of the aforementioned elements. In some specific embodiments, multiple metal ion dopants are selected from doping elements Al, V, Ni, Zn, and Y, each using oxides or nitrates at a corresponding atomic percentage of 0.015 to 0.03.

[0093] In some embodiments, the step of mixing the composite carbon source, the mixed metal source containing doped elements, and the calcined material is performed using wet ball milling, wherein the ball-to-material ratio is 3 / 1 to 6 / 1, the milling time is 2 to 6 hours, and the milling solvent is pure water or a mixture of water and anhydrous ethanol. In some specific embodiments, wet ball milling is used, wherein the ball-to-material ratio is 5 / 1, and the milling time is 4 hours.

[0094] In some embodiments, the solid content of the slurry obtained by mixing is 40% to 50%, and the particle size D of the slurry is... 50 The range is 0.3μm to 0.6μm.

[0095] In some embodiments, prior to granulation, slurries of different particle sizes are mixed in a specific ratio, wherein particle size D 50 The slurry with a particle size of 0.28μm to 0.32μm accounts for 20% to 30%, and the particle size D 50 The slurry with a particle size of 0.58μm to 0.62μm accounts for 70% to 80%.

[0096] Furthermore, after the particle size meets the requirements, D will be... 50 The range is 0.28 μm to 0.32 μm and D 50The slurry with a particle size of 0.58μm to 0.62μm is mixed evenly at a ratio of 20% to 30% to 70% to 80%, and then spray-dried for granulation.

[0097] In some embodiments, the secondary sintering temperature is 750℃~800℃, the heating rate is 5℃ / min~7℃ / min, and the time is 10h~16h.

[0098] In some specific embodiments, the secondary sintering temperature includes, but is not limited to, typical but limiting values ​​such as 750°C, 760°C, 770°C, 780°C, 790°C, and 800°C; the time includes, but is not limited to, typical but non-limiting values ​​such as 10h, 11h, 12h, 13h, 14h, 15h, and 16h.

[0099] The third aspect of this application discloses a lithium-ion battery positive electrode sheet, comprising the above-mentioned gradient-doped lithium manganese iron phosphate positive electrode material, a conductive agent, and a binder.

[0100] The lithium-ion battery positive electrode sheet provided in the third aspect of this application comprises the above-mentioned high-performance gradient-doped lithium manganese iron phosphate positive electrode material. Combined with a conductive agent and a binder, it can form a good electrode structure, ensuring the conductivity and stability of the electrode.

[0101] The fourth aspect of this application discloses a lithium-ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode adopts the above-mentioned lithium-ion battery positive electrode sheet.

[0102] The lithium-ion battery provided in the fourth aspect of this application uses this positive electrode sheet. Due to the improved performance of the positive electrode material, the battery as a whole has higher energy density, longer cycle life and better rate performance. It has a wider application prospect in the fields of new energy vehicles and energy storage systems and can meet the market demand for high-performance lithium-ion batteries.

[0103] The following description is based on specific embodiments.

[0104] Example 1

[0105] This embodiment provides a gradient-doped lithium manganese iron phosphate cathode material and its preparation method.

[0106] The gradient-doped lithium manganese iron phosphate cathode material is HeGD-LiMn. 0.6 Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02)PO4; (where HeGD represents high-entropy gradient doping); other physical properties of the sample are shown in Table 1.

[0107] Its preparation method includes the following steps:

[0108] (1) Lithium acetate (lithium source), manganese acetate (manganese source), ferrous oxalate (iron source), and ammonium dihydrogen phosphate (phosphorus source) were mixed in a molar ratio of 1.05:0.6:0.3:1.03. Citric acid was used as a chelating agent, ascorbic acid as a stabilizer, glucose as a carbon source and reducing agent, and water as a solvent. (The amount of glucose added was based on the carbon content after calcination not exceeding 0.1%. The doping elements Al, V, Ni, Zn, and Y were respectively doped with aluminum nitrate (aluminum source), vanadium acetylacetonate (vanadium source), nickel acetate (nickel source), zinc acetate (zinc source), and yttrium nitrate (yttrium source) at a corresponding atomic percentage of 0.005.) The following steps were followed: ① Prepare a metal cation-citric acid complex solution and adjust the pH of the solution to around 4 with ammonia water; ② Add lithium acetate, ammonium dihydrogen phosphate, and glucose, and adjust the pH of the solution to around 5.2 with ammonia water; ③ Evaporate the solvent in a water bath and gel the solution; ④ Vacuum dry to obtain the corresponding low-doped LMFP precursor.

[0109] (2) The LMFP low-doped precursor obtained in step (1) is crushed and then calcined at 550°C for 10 hours. The heating rate is controlled at 6°C / min. The calcined material is then crushed.

[0110] (3) Disperse the first-burned pulverized material from step (2) with a certain amount of composite carbon source (glucose + PEG, the amount added is to ensure that the carbon content of the finished product after the second burning reaches 1.4%) and metal ion dopant (doping elements Al, V, Ni, Zn, and Y are respectively used as dopant with aluminum source aluminum nitrate, vanadium source acetylacetone, nickel source nickel acetate, zinc source zinc acetate, and yttrium source yttrium nitrate at a corresponding atomic percentage of 0.015) in an appropriate amount of water, and ball mill and mix them (the amount of water added is to ensure that the solid content of the slurry reaches 40%, and the particle size of the ball milled slurry D) 50 The particle sizes were controlled within 0.28μm~0.32μm and 0.58μm~0.62μm respectively. After the particle size met the requirements, D... 50 : 0.28μm~0.32μm and D 50 The slurry with a particle size of 0.58μm to 0.62μm is mixed evenly at a ratio of 20% to 30% to 70% to 80%, and then spray-dried for granulation.

[0111] (4) The material spray-dried in step (3) is subjected to a second sintering at 780℃ for 16 hours, with the heating rate controlled at 6℃ / min. The sintered material is then pulverized to obtain the gradient-doped lithium manganese iron phosphate cathode material HeGD-LiMn. 0.6 Fe 0.3 (Al0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 )PO4.

[0112] Example 2

[0113] This embodiment provides a gradient-doped lithium manganese iron phosphate cathode material and its preparation method.

[0114] The gradient-doped lithium manganese iron phosphate cathode material is HeGD-LiMn. 0.6 Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 PO4; other physical properties of the sample are shown in Table 1.

[0115] The preparation method includes the following steps:

[0116] (1) Lithium acetate (lithium source), manganese acetate (manganese source), ferrous oxalate (iron source), and ammonium dihydrogen phosphate (phosphorus source) were mixed in a molar ratio of 1.05:0.6:0.3:1.03 (the amount of glucose added was based on the carbon content after calcination not exceeding 0.1%). The doping elements Al, V, Ni, Zn, and Y were respectively doped with aluminum nitrate (aluminum source), vanadium acetylacetonate (vanadium source), nickel acetate (nickel source), zinc acetate (zinc source), and yttrium nitrate (yttrium source) at a molar atomic percentage of 0.02). Citric acid was used as a chelating agent, ascorbic acid as a stabilizer, glucose as a carbon source and reducing agent, and water as a solvent. The following steps were taken: ① Prepare a metal cation-citric acid complex solution and adjust the pH of the solution to around 4 with ammonia water; ② Add lithium acetate, ammonium dihydrogen phosphate, and glucose, and adjust the pH of the solution to around 5.2 with ammonia water; ③ Evaporate the solvent in a water bath and gel the solution; ④ Vacuum dry to obtain the corresponding low-doped LMFP precursor.

[0117] (2) The LMFP low-doped precursor obtained in step (1) is crushed and then calcined at 550°C for 10 hours. The heating rate is controlled at 6°C / min. The calcined material is then crushed.

[0118] (3) Disperse the first-burned pulverized material from step (2) with a certain amount of composite carbon source (glucose + PEG, the amount added is to ensure that the carbon content of the finished product after the second burn reaches 1.4%) in an appropriate amount of water, and ball mill and mix them (the amount of water added is to ensure that the solid content of the slurry reaches 40%, and the particle size D of the ball milled slurry is...). 50 The particle sizes were controlled within 0.28μm~0.32μm and 0.58μm~0.62μm respectively. After the particle size met the requirements, D... 50: 0.28μm~0.32μm and D 50 The slurry with a particle size of 0.58μm to 0.62μm is mixed evenly at a ratio of 20% to 30% to 70% to 80%, and then spray-dried for granulation.

[0119] (4) The material spray-dried in step (3) is subjected to a second sintering at 780℃ for 16 hours, with the heating rate controlled at 6℃ / min. The sintered material is then pulverized to obtain the gradient-doped lithium manganese iron phosphate cathode material HeDG-LiMn. 0.6 Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 )PO4.

[0120] Example 3

[0121] This embodiment provides a gradient-doped lithium manganese iron phosphate cathode material and its preparation method.

[0122] The gradient-doped lithium manganese iron phosphate cathode material is HeGD-LiMn. 0.6 Fe 0.3 (Al 0.02 V 0.02 Ti 0.02 Zr 0.02 La 0.02 PO4; the conventional physical properties of the samples are shown in Table 1.

[0123] Compared with Example 1, the preparation method is modified by changing "Al, V, Ni, Zn, Y in steps (1) and (3)" to "Al, V, Ti, Zr, La"; and the corresponding dopants are changed to "aluminum nitrate, vanadium acetylacetonate, titanium dioxide, zirconium acetylacetonate, and lanthanum nitrate as the corresponding raw materials", while other contents remain unchanged.

[0124] Example 4

[0125] This embodiment provides a gradient-doped lithium manganese iron phosphate cathode material and its preparation method.

[0126] The gradient-doped lithium manganese iron phosphate cathode material is HeGD-LiMn. 0.6 Fe 0.3 (Mg 0.02 V 0.02 Cr 0.02 Nb 0.02 La 0.02 PO4; the conventional physical properties of the samples are shown in Table 1.

[0127] Compared with Example 1, the preparation method is modified by changing "Al, V, Ni, Zn, Y in steps (1) and (3)" to "Mg, V, Cr, Nb, La" and the corresponding dopants are changed to "magnesium oxide, vanadium acetylacetonate, chromium nitrate, niobium pentoxide, lanthanum nitrate"; other contents remain unchanged.

[0128] Example 5

[0129] This embodiment provides a gradient-doped lithium manganese iron phosphate cathode material and its preparation method.

[0130] The gradient-doped lithium manganese iron phosphate cathode material is HeGD-LiMn. 0.55 Fe 0.3 (Al 0.03 V 0.03 Ni 0.03 Zn 0.03 Y 0.03 PO4; the conventional physical properties of the samples are shown in Table 1.

[0131] Compared with Example 1, the preparation method is modified as follows: step (1) "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.005" is changed to "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.0758"; step (3) "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.015" is changed to "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.0225" is used, and the rest remains unchanged.

[0132] Example 6

[0133] This embodiment provides a gradient-doped lithium manganese iron phosphate cathode material and its preparation method.

[0134] The gradient-doped lithium manganese iron phosphate cathode material is HeGD-LiMn. 0.5 Fe 0.3 (Al 0.04 V 0.04 Ni 0.04 Zn 0.04 Y 0.04 PO4; the conventional physical properties of the samples are shown in Table 1.

[0135] Compared with Example 1, the preparation method is modified as follows: step (1) "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.005" is changed to "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.01"; step (3) "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.015" is changed to "doping elements Al, V, Ni, Zn, and Y are respectively used as oxides or nitrates with a corresponding atomic percentage of 0.03" is used, and the rest remains unchanged.

[0136] Comparative Example 1

[0137] This comparative example provides a common doped lithium manganese iron phosphate cathode material and its preparation method.

[0138] The common doped lithium iron phosphate cathode material is LiMn 0.6 Fe 0.4 PO4. The typical physical properties of the samples are shown in Table 1.

[0139] The preparation method includes the following steps: (1) Lithium acetate (lithium source), manganese acetate (manganese source), ferrous oxalate (iron source), and ammonium dihydrogen phosphate (phosphorus source) are in a molar ratio of 1.05:0.6:0.3:1.03; citric acid is used as a chelating agent, ascorbic acid as a stabilizer, glucose as a carbon source and reducing agent, and water as a solvent; (the amount of glucose added is based on the carbon content after calcination not exceeding 0.1%), according to the following steps: ① Prepare a metal cation-citric acid complex solution, and adjust the pH of the solution to around 4 with ammonia water; ② Add lithium acetate (lithium source), ammonium dihydrogen phosphate (phosphorus source), and glucose (carbon source), and adjust the pH of the solution to around 5.2 with ammonia water; ③ Evaporate the solvent in a water bath and gel the solution; ④ Vacuum dry to obtain the corresponding precursor LMFP low-doped precursor.

[0140] (2) The LMFP precursor obtained in step (1) is crushed and then calcined at 550°C for 10 hours. The heating rate is controlled at 6°C / min. The calcined material is then crushed.

[0141] (3) Disperse the first-burned pulverized material from step (2) and a certain amount of composite carbon source (glucose and PEG, the amount added is to ensure that the carbon content of the finished product after second-burning is 1.4%) in an appropriate amount of water, and ball mill them together (the amount of water added is to ensure that the solid content of the slurry reaches 40%, and the particle size of the ball milled slurry is D). 50 The particle sizes were controlled within 0.28μm~0.32μm and 0.58μm~0.62μm respectively. After the particle size met the requirements, D... 50 : 0.28μm~0.32μm and D 50The slurry with a particle size of 0.58μm to 0.62μm is mixed evenly at a ratio of 20% to 30% to 70% to 80%, and then spray-dried for granulation.

[0142] (4) The material spray-dried in step (3) is subjected to a second sintering at 780℃ for 16 hours, with the heating rate controlled at 5℃~7℃ / min. The material from the second sintering is then pulverized to obtain the ordinary doped lithium manganese iron phosphate cathode material LiMn. 0.6 Fe 0.4 PO4.

[0143] Table 1

[0144]

[0145]

[0146] Performance testing

[0147] To verify the progressiveness of the embodiments of this application, the following performance tests were performed on the above embodiments and comparative examples:

[0148] (1) The HeGD-LiMn prepared in Example 1 0.6 Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 )PO4, HeD-LiMn prepared in Example 2 0.6 Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 )PO4, LiMn prepared in Comparative Example 1 0.6 Fe 0.4 PO4 was subjected to X-ray diffraction tests.

[0149] (2) The samples prepared in the examples and comparative examples were subjected to high-temperature coin cell cycle performance tests at 45°C.

[0150] Results Analysis

[0151] (1) The HeGD-LiMn prepared in Example 1 0.6 Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 )PO4, HeD-LiMn prepared in Example 2 0.6Fe 0.3 (Al 0.02 V 0.02 Ni 0.02 Zn 0.02 Y 0.02 )PO4, LiMn prepared in Comparative Example 1 0.6 Fe 0.4 X-ray diffraction tests were performed on PO4, and the XRD patterns are shown in the attached figure. Figure 1 As shown, the samples obtained are all olivine structures, and the diffraction peak positions of the examples are shifted compared to the comparative examples, indicating that high-entropy gradient doping has changed the microcrystalline structure.

[0152] (2) The samples prepared in the examples and comparative examples were subjected to high-temperature coin cell cycle performance tests at 45°C, as shown in Table 2.

[0153] Table 2

[0154]

[0155] According to Table 2, the analysis of the cycle performance data of Examples 1-6 and Comparative Example 1 shows that all examples exhibit significantly better battery performance than the comparative example. In the 1C rate cycle test, the discharge capacity retention rate of the example groups generally remained above 99% after 100 cycles, with Examples 3, 4, and 5 even showing a slight increase in capacity, demonstrating excellent cycle stability. In contrast, the capacity retention rate of Comparative Example 1 was only 85.8% after the same number of cycles, with a decay rate exceeding 14%, showing a significant performance disadvantage. Regarding voltage stability, the discharge voltage retention rate of the example groups was all above 99.3% (Example 3 reached 99.73%), while that of Comparative Example 1 dropped to 93.9%, indicating that the materials of the examples have better structural stability and less polarization.

[0156] Further analysis shows that the high performance of the Example Group is mainly reflected in three key dimensions: First, its charge-discharge efficiency is consistently maintained above 99.4% (up to 99.72%), far exceeding the 98.14% of Comparative Example 1, indicating that side reactions are effectively suppressed; Second, the first-cycle efficiency of Example 4 reaches 98.13%, the highest among all samples, reflecting its optimized interface characteristics; Third, the capacity and voltage retention rates show a high degree of synergy, with both in the Example Group decreasing by less than 1%, while Comparative Example 1 shows a simultaneous and significant decrease. This difference may be due to the fact that the Example Group's material is a high-entropy gradient-doped lithium manganese iron phosphate cathode material.

[0157] In summary, the "high initial efficiency (>98%) - high efficiency (>99.4%) - high retention rate (>99.7%)" three-in-one characteristics exhibited by the example group, especially Example 4, indicate that its material system has achieved breakthroughs in crystal structure stability, interfacial compatibility, and kinetic performance. This performance advantage may stem from the fact that the provided gradient-doped lithium manganese iron phosphate cathode material adopts a core-shell structure with a gradient-increasing distribution of mixed doping elements, creating a unique chemical environment within the material. On the one hand, the change in concentration gradient effectively alleviates lattice distortion problems, enhances the structural stability of the material, and reduces phase transitions and volume changes during cycling, thereby significantly improving the material's cycling performance. On the other hand, the gradient distribution of doping elements optimizes the charge transport path, reduces asynchronous reactions between particles, effectively suppresses voltage decay during charging and discharging, and increases energy density. Simultaneously, the introduction of high entropy can suppress the formation of Mn... 3+ The Jahn-Teller distortion caused by the disproportionation reaction improves the structural stability of the material and prevents the accumulation of dopants during cycling. On the other hand, the high-entropy environment may reduce the activation energy of Li+ migration and improve the kinetics, which is beneficial to improving the overall performance of lithium manganese iron phosphate cathode materials.

[0158] The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A gradient-doped lithium manganese iron phosphate cathode material, characterized in that, The gradient-doped lithium manganese iron phosphate cathode material includes mixed doping elements, which include at least four different elements; and the gradient-doped lithium manganese iron phosphate cathode material forms a core-shell structure based on the concentration variation of the mixed doping elements, with the mixed doping elements distributed in a gradient increasing manner along the core-shell structure; the gradient increasing distribution means that the concentration of the mixed doping elements gradually increases from the core to the shell. The mixed doping elements include at least the following four different elements: At least one of the rare earth elements La and Y; At least one of the transition metal elements Ti, V, Ni, and Cr; At least one of the transition metal elements Zn, Zr, and Nb; At least one of the light metal elements Mg and Al; Furthermore, the atomic percentage of each element is 0.02-0.

04.

2. The gradient-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The mixed doping elements satisfy the following conditions: (a) In the kernel interface region: doping concentration is 1%~5%; (b) In the intermediate transition region: the doping concentration is 2.5% to 10%; (c) In the shell interface region: the doping amount is 5%~15%.

3. The gradient-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The configurational entropy ΔS of the gradient-doped lithium manganese iron phosphate cathode material is 1.0 R~1.5 R.

4. The gradient-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The particle size distribution of the gradient-doped lithium manganese iron phosphate cathode material satisfies: D 10 ≤0.5μm, D 50 ≤1.0μm, D 90 ≤4.0μm.

5. The gradient-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The gradient-doped lithium manganese iron phosphate cathode material further includes a carbon coating layer, wherein the thickness of the carbon coating layer is 4nm~8nm; Based on the total mass of the gradient-doped lithium manganese iron phosphate cathode material as 100%, the carbon content is 1.2 wt% to 1.5 wt%.

6. The gradient-doped lithium manganese iron phosphate cathode material according to any one of claims 1 to 5, characterized in that, The mixed doping elements are selected from combinations of Al, V, Ni, Zn, and Y.

7. A method for preparing a gradient-doped lithium manganese iron phosphate cathode material as described in any one of claims 1-6, characterized in that, Includes the following steps: Provide precursors containing low concentrations of mixed doped elements; The precursor is subjected to a sintering process to obtain a sintered material. The composite carbon source, the mixed metal source containing doped elements, and the sintered material are mixed, granulated, and subjected to a secondary sintering process to obtain a gradient-doped lithium manganese iron phosphate cathode material.

8. The method for preparing the gradient-doped lithium manganese iron phosphate cathode material according to claim 7, characterized in that, The precursor containing a low concentration of mixed doped elements has a content of 1.0% to 5.0% for the mixed doped elements; and / or, With the total mass of the calcined material being 100%, the carbon content being 0.01 wt%~0.1 wt%; and / or, The composite carbon source is selected from at least two of glucose, PEG, and oleic acid.

9. The method for preparing the gradient-doped lithium manganese iron phosphate cathode material according to claim 7, characterized in that, The primary sintering temperature is 500℃~600℃, the heating rate is 5℃ / min~7℃ / min, and the time is 6 h~10 h; and / or, The secondary sintering temperature is 750℃~800℃, the heating rate is 5℃ / min~7℃ / min, and the time is 10 h~16 h; and / or, In the step of mixing the composite carbon source, the mixed metal source containing doped elements, and the calcined material, a wet ball milling process is used, wherein the ball-to-material ratio is 3 / 1 to 6 / 1, the ball milling time is 2 to 6 hours, and the ball milling solvent is pure water or a mixture of water and anhydrous ethanol.

10. The method for preparing the gradient-doped lithium manganese iron phosphate cathode material according to claim 7, characterized in that, The slurry obtained by mixing has a solid content of 40% to 50%, and the particle size D of the slurry is... 50 The micrometer diameter is 0.3 μm to 0.6 μm; and / or, Before granulation, slurries of different particle sizes are mixed in a certain proportion, wherein particle size D 50 The slurry with a particle size of 0.28μm to 0.32μm accounts for 20% to 30%, and the particle size D 50 The proportion of slurry with a particle size of 0.58μm to 0.62μm is 70% to 80%.

11. A positive electrode sheet for a lithium-ion battery, characterized in that, It comprises the gradient-doped lithium manganese iron phosphate cathode material, conductive agent, and binder as described in any one of claims 1 to 6.

12. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode is the lithium-ion battery positive electrode sheet as described in claim 11.

Citation Information

Patent Citations

  • High-entropy doped lithium ferric manganese phosphate positive electrode material with hierarchical pore structure and preparation method of high-entropy doped lithium ferric manganese phosphate positive electrode material

    CN117038909A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN119725439A